Analisis Tarif Penggunaan Bike-Sharing Berdasarkan Ability-to-Pay dan Willingness-to-Pay di Kampus Institut Teknologi Kalimantan - Hadid, Muhammad; Anronius, Obed (Jurnal Aplikasi Teknik Sipil, 2025)
ITK needs to provide a facility that restricts private mode that operates on campus. Bike-sharing encourages greener mobility in the campus area. This study aims to get a model of bike-sharing users, with the market being the student who lives surrounding the campus area. The method uses both conventional and electric bikes' ability-to-pay and willingness-to-pay of students toward bike-sharing. The results show that the student's highest potency of the bike-sharing user is 82%, and the lowest is 44%. The highest potency of the electric bike for bike-sharing is 81%, and the lowest potency is 31%. The result also indicates that the students tend to use bike-sharing and consider tariffs rather than payment methods for conventional and electric bikes. The ability-to-pay and willingness-to-pay indicate the students are a choice raider. The value of ability-to-pay shows it is higher than willingness-to-pay towards the bike-sharing facility.